Phase separation between nucleoid and cytoplasm in Escherichia coli as defined by immersive refractometry. - Valkenburg, J A (1984)
The refractive indices of nucleoid and cytoplasm in Escherichia coli were derived theoretically and experimentally. For the theoretical estimates, we made use of the known macromolecular composition of E. coli B/r (G. Churchward and H. Bremer, J. Theor. Biol. 94:651-670, 1982) and of estimates of cell and nucleoid volumes. These were obtained from micrographs of living bacteria made with a confocal scanning light microscope. The theoretical values were calculated, assuming that all DNA occurred in the nucleoid and that all protein and RNA occurred in the cytoplasm. Comparison with experimental refractive index values directly obtained by immersive refractometry showed that, besides its DNA, the nucleoid must contain an additional amount of solids equivalent to 8.6% (wt/vol) protein. With the nucleoid containing 6.8% (wt/vol) DNA and 8.6% (wt/vol) protein and the cytoplasm containing 21% (wt/vol) protein and 4% (wt/vol) RNA, a mass difference is obtained, which accounts for the phase separation observed between the nucleoid and cytoplasm in living cells by phase-contrast microscopy. The decrease in the refractive index of the nucleoid relative to that of the cytoplasm observed upon, for instance, OsO4 fixation was interpreted as being indicative of the loss of protein content in the nucleoid.